Evaluation study on experimental and theoretical simulation elastic properties analysis of neodymium-doped magnesium borotellurite glasses - Abuallan, Mohammad Ayman; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Yaakob, Yazid; Sarmani, Abdul Rahman; Cheong, Wei Mun; Loh, Zhi Wei (Elsevier, 2023)
This study investigated the elastic, structural, and physical of magnesium borotellurite glasses modified with neodymium oxide. The bulk sample's density increased from 3.97 g/cm3 to 4.10 g/cm3 by raising the Nd2O3 concentration while molar volume illustrated a contrary trend. X-ray diffraction analysis proves the amorphous state of glasses and elastic moduli demonstrated a linear increase with the increment of Nd2O3. The elastic modulus shows and increasing trend with the progress of neodymium concentration. The elastic moduli from Makishima-Mackenzie and Rocherulle’s model followed the same trend as the experimental values. The results show that the MBTNd-3 glass sample currently has the optimum properties, indicating that the MBTNd-3 glass sample is potentially used for high-strength glass applications.